Disrupting AMPK-Glycogen Binding in Mice Increases Carbohydrate Utilization and Reduces Exercise Capacity - Janzen, Natalie R.; Whitfield, Jamie; Murray-Segal, Lisa; Kemp, Bruce E.; Hawley, John A.; Hoffman, Nolan J. (Frontiers in Physiology, 2022)
The AMP-activated protein kinase (AMPK) is a central regulator of cellular energy balance and metabolism and binds glycogen, the primary storage form of glucose in liver and skeletal muscle. The effects of disrupting whole-body AMPK-glycogen interactions on exercise capacity and substrate utilization during exercise in vivo remain unknown. We used male whole-body AMPK double knock-in (DKI) mice with chronic disruption of AMPK-glycogen binding to determine the effects of DKI mutation on exercise capacity, patterns of whole-body substrate utilization, and tissue metabolism during exercise. Maximal treadmill running speed and whole-body energy utilization during submaximal running were determined in wild-type (WT) and DKI mice. Liver and skeletal muscle glycogen and skeletal muscle AMPK α and β2 subunit content and signaling were assessed in rested and maximally exercised WT and DKI mice. Despite a reduced maximal running speed and exercise time, DKI mice utilized similar absolute amounts of liver and skeletal muscle glycogen compared to WT. DKI skeletal muscle displayed reduced AMPK α and β2 content versus WT, but intact relative AMPK phosphorylation and downstream signaling at rest and following exercise. During submaximal running, DKI mice displayed an increased respiratory exchange ratio, indicative of greater reliance on carbohydrate-based fuels. In summary, whole-body disruption of AMPK-glycogen interactions reduces maximal running capacity and skeletal muscle AMPK α and β2 content and is associated with increased skeletal muscle glycogen utilization. These findings highlight potential unappreciated roles for AMPK in regulating tissue glycogen dynamics and expand AMPK’s known roles in exercise and metabolism.